Big data for dummies - Hurwitz, Judith (New Delhi New Delhi, 2017)
Explains big data in detail and discusses how to select and implement a solution, security concerns to consider, data storage and presentation issues, analytics, and much more.
Grasping the fundamentals of big data -- Examining big data types -- Old meets new: distributed computing -- Digging into the big data technology components -- Virtualization and how it supports distributed computing -- Examining the cloud and big data -- Operational databases -- MapReduce fundamentals -- Exploring the world of Hadoop -- The Hadoop foundation and ecosystem -- Appliances and big data warehouses -- Defining big data analytics -- Understanding text analytics and big data -- Customized approaches for analysis of big data -- Integrating data sources -- Dealing with real-time data streams and complex event processing -- Operationalizing big data -- Applying big data within your organization -- Security and governance for big data environments -- The importance of big data to business -- Analyzing data in motion: a real-world view -- Improving business processes with big data analytics: a real-world view -- Ten big data best practices -- Ten great big data resources -- Ten big data do's and don'ts.
Includes index.
Keywords: Big data -- Social aspects; Internet -- Social aspects; Electronic information resources -- Social aspects; Technological innovations -- Social aspects; Social change